BELA NEGARA SEBAGAI LANDASAN PENGEMBANGAN PARIWISATA DI KABUPATEN SLEMAN - Agussalim, Agussalim (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
State Defense is not only related to national defense and security, but can also be applied in tourism development to preserve nature, maintain local culture, and strengthen the sense of nationality of the community. Sleman Regency of Yogyakarta is one of the regencies that conducts sustainable tourism development by applying the principles and values of State Defense as a foundation in its development. With a diverse social structure of economic, ethnic, and religious levels, the diverse community members can synergize with the government in an effort to develop sustainable tourism in Sleman Regency. On that basis, the purpose of this research is to explain what causes the diverse communities to synergize in developing sustainable tourism. To answer the problem, this research uses a state defense approach in its analysis, using descriptive qualitative research methods and data collection using library methods. The findings of this research are that the community can work together and at the same time can support local government programs in developing sustainable tourism because tourism development in Sleman Regency is based on the principles and values of state defense, so that its people prioritize a strong tolerant life, even though they are diverse in their ethnicity and religion. The conclusion is that the development of sustainable tourism based on the principles and basic values of State Defense can provide economic benefits for the community, preserve nature and local culture, and increase the awareness and sense of nationality of the community.